Tracking fluorescent and ferrimagnetic sediment tracers on an energetic ebb-tidal delta to monitor grain size-selective dispersal. (15th October 2021) - Pearson, Stuart G.; van Prooijen, Bram C.; Poleykett, Jack; Wright, Matthew; Black, Kevin; Wang, Zheng Bing
Abstract: Sediment tracer studies use uniquely identifiable particles to track the pathways and fate of individual sand or silt grains in marine environments. These techniques are best applied to assess connectivity between potential sediment sources and sinks, such as between a sand nourishment and an ecologically sensitive area. Significant challenges exist when applying sediment tracing techniques to further understanding of systems with complicated hydrodynamic, sediment, and morphological regimes. Ebb-tidal deltas are highly dynamic coastal environments shaped by the complex interplay of waves and tides, but have been under-explored. In this study, we use dual signature (fluorescent and ferrimagnetic) sediment tracers to simulate the dispersal of dredged sediment placed as a sand nourishment on an energetic ebb-tidal delta (at Ameland Inlet, the Netherlands). After deployment, sediment dispersal and grain size sorting behaviour were monitored via the collection of seabed grab samples and magnetic sampling of sediment transported in suspension. The tracer content within collected samples were put in context with hydrodynamic conditions observed during the study period. Here we show that the use of such dual signature tracers, in addition to novel tracer recovery and analysis techniques, enables the dispersal of sediment to be monitored even in such complex settings and energetic conditions as an ebb-tidal delta. Our observations show that tracers transported in suspension are significantly finer than tracers that accumulated in the seabed. These suggest that preferential transport as a function of grain size is a key process in shaping the morphology of ebb-tidal deltas and thus governing the dispersal of sand nourishments there. The findings of this study and the approach used here provide valuable tools for assessing the baseline conditions of complex coastal environments today, and for planning the interventions which may be necessary in future responses to climate change. Lessons learned from the application of sediment tracers in this study are provided to assist future researchers and practitioners in applying this technique in dynamic coastal environments. Highlights: Large-scale sediment tracer study conducted on a highly dynamic ebb-tidal delta. Despite the challenges presented by such an energetic setting, tracer was recovered. Tracer recovery and processing were enhanced by its fluorescence and ferrimagnetism. Tracking grain size of recovered tracers is essential for interpretation. Tracers prove to be useful tool for sand nourishments planning and monitoring.